A Way towards Economic Growth in Pakistan: Role of Worker’s Remittances Revisited - Ali, Hina; Tahir, Saba (Pakistan Journal of Humanities and Social Sciences, 2017)
This research is directed to study the role of remittances in the economic growth of Pakistan. In Pakistan workers, remittances are considered a second-largest source of finance after FDI. In this study, the relationship between worker's remittances and economic development in Pakistan is estimated by using the Ordinary Least Square (OLS) technique. Data is taken in time series for the period of 37 years from 1976 to 2013 from World Bank, economic surveys, and Stat bank of Pakistan. This research showed that worker’s remittances are positive as well as significant with GDP growth and also playing a dynamic part in the economy of Pakistan. Savings (SAV) and Foreign direct investment (FDI) have positive and significant impacts on economic development. Therefore, the study recommends that there should be a proper setup that will help to attract more workers remittances into the economy. There is a need for such an official financial sector that inspires recipients to invest their savings into a productive sector that would result in economic growth.